Electric field influence on the stability and the soot particles emission of a laminar diffusion flame. Issue 2 (1st February 2019) - Gillon, Pascale; Gilard, Virginie; Idir, Mahmoud; Sarh, Brahim
ABSTRACT: Influence of electric fields on flames has been studied for many years and the ionic wind constitutes the main explanation of the observed effects on the flame structure and pollutant emissions. However, previous works have been limited to small flames. The interaction mechanisms of an electric field with longer flames, involving both ionic wind and buoyancy are not fully identified. In the present paper, the effects of a D.C. electric field on a laminar 88-mm-long ethylene diffusion flame burning in ambient air are investigated. Based on the calculated electric field configuration, the influence of both downward and upward electric field is compared via imaging, electrical diagnostic and soot measurements. The application of a negative (directed downstream) electric field triggers a flickering instability and an electric instability at higher field strength, in which self-sustained flame oscillations of flame length directly affect ion current. Conversely, the flame is stabilized by a positive electric field. In-situ soot volume fraction measurements show that the electric field decreases the average soot volume fraction measured on a stable flame axis, whereas flame oscillations lead to a sooting flame.